PVDF/HMO ultrafiltration membrane for efficient oil/water separation - Nurul Hafiza, Ismail; Wan Norharyati, Wan Salleh; Nor Asikin, Awang; Siti Zu Nurain, Ahmad; Nurafiqah, Rosman; Norazlianie, Sazali; Ismail, A. F. (Taylor & Francis, 2019)
In this research, hydrous manganese oxide (HMO) nanoparticles was adopted in polyvinylidene fluoride (PVDF) to improve the ability of the mixed matrix membrane (MMM) to separate oil/water emulsions. The MMMs – which were added with various amounts of HMO loading (3, 5, 7 and 10 wt%) – were characterized for its physicochemical properties, morphological structure, and nanoparticles dispersion of the PVDF/HMO membrane. Evidently, the presence of these nanoparticles increased the hydrophilicity and oleophobicity of the PVDF/HMO membrane as compared to those of the pristine PVDF. Concurrently, the water contact angle was reduced from 99 to 58 while oil contact angle increased from 0 to 35 . The presence of -OH groups and Mn element channeling the PVDF/HMO membrane wetting properties, which in turn improved the membrane’s affinity towards water molecules and aversion to oil droplets. The PVDF/HMO membrane that contained 10 wt% of HMO loading exhibited a water flux (402 L/m2 h) – 10 times greater than the pristine PVDF membrane with 93% oil rejection rate.